2020
DOI: 10.1007/s40415-020-00585-9
|View full text |Cite
|
Sign up to set email alerts
|

Natural recovery of plant species diversity in secondary forests in Eastern Amazonia: contributions to passive forest restoration

Abstract: Natural regeneration is important in the context of the strategies to recover native vegetation in Brazil and of the international commitments of forest restoration undertaken by the country. However, trajectories of recovery can be highly variable and context-dependent, demanding studies to foster the use of secondary forests in restoration. Here, we describe the natural recovery of plant diversity in a chronosequence (5-21 years old) and how it is influenced by age of the regenerating forests. For this, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…The recovery of 90% of diversity in less than 20 years (figure 3(B)) shows the very high resilience of West African forest biodiversity. Similar results have already been observed in neotropical forests where only 20 years were sufficient for secondary forests to recover 90% of their species richness and diversity (Lennox et al 2018, Barros et al 2020. The fast recovering of diversity may be linked to the intermediate disturbance hypothesis where biodiversity quickly peaks in recovering forests because of the cooccurrence of persisting pioneer species and shadetolerant species that established in the shade of these pioneers (Rozendaal et al 2019).…”
Section: Recovery Rates Depend On Forest Attributessupporting
confidence: 72%
“…The recovery of 90% of diversity in less than 20 years (figure 3(B)) shows the very high resilience of West African forest biodiversity. Similar results have already been observed in neotropical forests where only 20 years were sufficient for secondary forests to recover 90% of their species richness and diversity (Lennox et al 2018, Barros et al 2020. The fast recovering of diversity may be linked to the intermediate disturbance hypothesis where biodiversity quickly peaks in recovering forests because of the cooccurrence of persisting pioneer species and shadetolerant species that established in the shade of these pioneers (Rozendaal et al 2019).…”
Section: Recovery Rates Depend On Forest Attributessupporting
confidence: 72%
“…The structure and diversity of secondary forests can be recovered over time [22,29]. In this study, we found that species richness increased throughout chronosequence, a typical pattern in successional forests [59,61].…”
Section: Abandonment Time and Distance To The Forest Edgementioning
confidence: 49%
“…Moreover, in late succession, seed sources and their dispersal are the most important biotic factors as they are more limited by distance [49]. In addition, passive restoration is considered a cost-effective restoration strategy in comparison with active restoration [22]. However, passive restoration is a slow process, and it may take decades or longer to achieve desired ecosystem functions or species compositions without active restoration [64].…”
Section: Abandonment Time and Distance To The Forest Edgementioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, new forms of forest and ecological restoration that offer ways of converting degraded tropical forests have been tested. These restoration techniques include improvements in secondary forests management, reforestation, and enrichment planting as more complex reforestation where forest cover has been lost (Matos et al 2019;Barros et al 2020). While forest loss continues in Brazil at variable rates, techniques are implemented to develop secondary forests where primary forests have been completely removed by human processes.…”
Section: Introductionmentioning
confidence: 99%